Cover Image, Volume 11, Issue 3. (March 2017) - Chung, Eun Ji; Sugimoto, Matthew J.; Koh, Jason L.; Ameer, Guillermo A.
Abstract : The cover image, by Eun Ji Chung et al., is based on the Research Article A biodegradable tri-component graft for anterior cruciate ligament reconstruction, DOI:10.1002/term.1966 .